Effect of 1800°C annealing on oxidation behaviour of silicon carbide ceramics derived from polycarbosilane. (April 2013) - Ma, Y; Chen, Z H
Abstract : The effect of 1800°C annealing on the oxidation behaviour of silicon carbide ceramics derived from polycarbosilane (PCS) was investigated by thermogravimetric analysis when the annealing atmosphere was Ar. These results indicated that the silicon carbide ceramics before and after 1800°C annealing both started to oxidise near 600°C. However, the oxidation behaviours of the silicon carbide ceramics were remarkably different above 600°C due to the microstructure changes during 1800°C annealing. The silicon carbide phase and the free carbon phase were almost oxidised together in the silicon carbide ceramics derived from PCS at 1200°C, while the free carbon phase had been mostly oxidised before the silicon carbide phase began to oxidise in the 1800°C annealing silicon carbide ceramics. Moreover, after oxidation, there were many nanopores present in the skeletons of the silicon carbide ceramics with 1800°C annealing.